The overall properties of intermediate-age galactic open clusters: fundamental parameters of NGC 2627 - Piatti, Andres Eduardo (2004)
We present CCD VIKC and CMT1 photometry in the field of the open cluster NGC 2627. A mean cluster metallicity of [Fe/H] = -0.12 +/- 0.08 was derived from four Washington abundance indices. Through comparison of the cluster CMDs with theoretical isochrones, we derived reddening, distance and age. We examined the overall properties of the intermediate-age open clusters and we identified four peaks of cluster formation at 0.7-0.8, 1.0-1.1, 1.6-1.7 and 2.0-2.1 Gyr. A radial abundance gradient of -0.08 dex/kpc was derived, but no clear evidence for a Z gradient was found.